Prognostic role of hs-CRP before and after Percutaneous Coronary Intervention in Patients with Stable Angina Pectoris - Das, Mrinal Kanti; Safiuddin, Mohammad; Zaman, SM Mustafa; Rashid, Khondoker Harun or; Chowdhury, Mohammad Saiful Islam; Jamil, Abu Bakar Md; Sultan, Md Ashraf Uddin (University Heart Journal, 2022)
Background and Objectives: Myocardial injury after percutaneous coronary intervention (PCI) occurs frequently and it is associated with an adverse clinical outcome. Mechanical factors have been implicated in this complication and the role of inflammation has not yet been clearly determined. We evaluated the effect of an inflammatory response during PCI on periprocedural myocardial injury. Subjects and Methods: This prospective observational study was conducted in the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh over a period between July’2012 to June’2013. A total of 200 patients studied who underwent elective coronary stenting. For the exclusion of mechanical injury to the myocardium, we excluded those patients who developed complications during PCI. The inflammatory response to PCI was calculated as the difference between the peak postprocedural hs-CRP level and the preprocedural hs-CRP level . We divided the patients according to the median value of hs- CRP: Group I <3 mg/L and Group II >3 mg/L. Results: Postprocedural TnI elevation was were observed in 72 (36%) patients. The baseline clinical and angiographic characteristics were not difference between the two groups. The incidence of any TnI elevations was higher in the Group II than that in Group I (19.8% vs 42.6%, respectively, p<0.001). The incidences of TnI levels over 3 times the upper normal limit and 5 times the upper normal limit were also higher in Group II than in Group I (11.2% vs 21.7%, respectively, p=0.031, for a TnI level 3 times the upper normal limit, and 6.0% vs 13.9%, respectively, for a TnI level 5 times the upper normal limit. Multivariate analysis revealed that postprocedural hs- CRP elevation in high risk group were the significant independent predictors of postprocedural TnI elevation. Conclusion: Elevated hs-CRP levels were associated with a higher risk of postprocedural troponin elevation in patients undergoing uncomplicated PCI. These results emphasized the role of inflammation in the pathogenesis of periprocedural myocardial injury. Measuring of hs-CRP either preprocedural or postprocedural in high risk patients is useful for predicting early cardiovascular events. University Heart Journal 2022; 18(2): 87-92